2015
DOI: 10.1159/000381185
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Thyroid Carcinoma in Patients with Graves' Disease: The Role of Ultrasound in Selecting Patients for Definitive Therapy

Abstract: Background/Aims: Pediatric Graves' disease (GD) accounts for 10-15% of all thyroid disorders in patients ≤18 years and is treated with antithyroid medication or definitive therapy [radioactive iodine (RAI) ablation vs. surgery]. Patients with GD may have concurrent differentiated thyroid cancer (DTC). DTC prevalence in pediatric GD is not well established. We examined the prevalence of DTC in pediatric GD and the role of preoperative thyroid ultrasound (US) in selecting the appropriate definitive therapy. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…Proposed mechanisms for the association between Hashimoto’s thyroiditis and PTC include over-production of thyroid stimulating hormone (TSH) or chronic inflammation resulting in proliferation, angiogenesis, and/or reduced apoptosis [12]. Data in pediatric Graves’ disease is more limited with respect to malignancy risk, with reports of follicular-cell derived thyroid cancer ranging from <1% to 22% of patients undergoing definitive surgical therapy; this number further decreases if non-surgically treated Graves patients are included in the denominator [20,21,22]. The link between iodine deficiency and FTC has also been more extensively studied in adults; however, of the few studies published in the pediatric population, several have suggested that iodine intake may be protective in the setting of radiation exposure and the development of PTC [13,23,24,25].…”
Section: Background and Epidemiologymentioning
confidence: 99%
“…Proposed mechanisms for the association between Hashimoto’s thyroiditis and PTC include over-production of thyroid stimulating hormone (TSH) or chronic inflammation resulting in proliferation, angiogenesis, and/or reduced apoptosis [12]. Data in pediatric Graves’ disease is more limited with respect to malignancy risk, with reports of follicular-cell derived thyroid cancer ranging from <1% to 22% of patients undergoing definitive surgical therapy; this number further decreases if non-surgically treated Graves patients are included in the denominator [20,21,22]. The link between iodine deficiency and FTC has also been more extensively studied in adults; however, of the few studies published in the pediatric population, several have suggested that iodine intake may be protective in the setting of radiation exposure and the development of PTC [13,23,24,25].…”
Section: Background and Epidemiologymentioning
confidence: 99%
“…In patients with Graves' disease, the likelihood of thyroid cancer increases in the presence of one or more thyroid nodules at ultrasound imaging, with a cancer risk rate of 22% compared with 5.1% in the absence of nodules [3]. To date there are few data on the co-presence of Graves' disease and DTC in children and adolescents [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with Graves' disease periodic ultrasound followup is recommended to rule out nodular thyroid disease. In adult patients with hyperthyroidism, recent studies have shown an increase in the rate of differentiated thyroid cancer (DTC), with an incidence of 4.7-81.1%, especially in the presence of nodules; to date very few data are present for the pediatric age [3][4][5][6][7]. The most represented type of DTC is papillary microcarcinoma and the co-presence of Graves' disease does not appear to be associated with more aggressive tumor behaviour [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative fine needle aspiration biopsy detected four concurrent DTCs, preoperatively. Thyroid ultrasound was found to be an efficient tool for selecting patients for thyroidectomy vs RAI ablation ( 57 ). In contrast, MacFarland et al ( 31 ) found that concurrent DTC in paediatric patients with GD is not associated with a greater disease burden at presentation and shows no significant differences in 2-year outcomes compared with DTC alone.…”
Section: Special Statesmentioning
confidence: 99%